Inflectional Morphemes and Their Grammatical Functions in Owl City`s Album Ocean Eyes (2009) - Hidayat, Muhammad Raihan; Rosalinah, Yanti (Kajian Linguistik dan Sastra, 2026)
This study investigates the grammatical functions and stylistic implications of inflectional morphemes in Owl City’s Ocean Eyes album (2009). Employing a qualitative descriptive design, the research analyzes how these morphological markers contribute to the lyrical structure based on the framework of Fromkin, Rodman, and Hyams (2018). Data were collected from official song lyrics, resulting in 151 identified words containing inflectional affixes. The findings reveal a significantly uneven distribution: noun plural markers are the most dominant category (63.8%), followed by verb inflections (32.5%) and adjective inflections (approximately 4%). The high frequency of plural nouns creates the vast, concrete imagery characteristic of the "dream pop" genre. Additionally, the predominance of third-person singular -s and present participle -ing establishes a narrative tone of immediacy and continuous action. The study concludes that inflectional morphemes in Ocean Eyes function not only to maintain grammatical accuracy but also to construct the album's distinct vivid and surreal aesthetic.  Abstrak Penelitian ini mengkaji fungsi gramatikal dan implikasi stilistika dari morfem infleksional dalam lirik album Ocean Eyes (2009) karya Owl City. Dengan menggunakan desain penelitian deskriptif kualitatif, studi ini menganalisis bagaimana penanda morfologis tersebut berkontribusi pada struktur lirik berdasarkan kerangka teori Fromkin, Rodman, dan Hyams (2018). Data dikumpulkan dari lirik lagu resmi, menghasilkan 151 kata yang mengandung afiks infleksional. Temuan menunjukkan distribusi yang sangat tidak merata: penanda jamak nomina adalah kategori paling dominan (63,8%), diikuti oleh infleksi verba (32,5%) dan infleksi adjektiva (sekitar 4%). Tingginya frekuensi nomina jamak menciptakan citraan konkret dan luas yang menjadi ciri khas genre "dream pop". Selain itu, dominasi orang ketiga tunggal -s dan partisipel kini -ing membangun nada naratif yang terasa langsung dan berkelanjutan. Studi ini menyimpulkan bahwa morfem infleksional dalam Ocean Eyes berfungsi tidak hanya untuk menjaga akurasi tata bahasa, tetapi juga untuk membangun estetika visual dan surealis yang khas dalam album tersebut.